Endothelial nitric oxide synthase gene intron 4 variable number tandem repeat polymorphism in β-thalassemia major: relation to cardiovascular complications. Issue 4 (June 2015) - Tantawy, Azza A.G.; Adly, Amira A.M.; Ismail, Eman A.; Aly, Shereen H.
Abstract : Endothelial nitric oxide synthase (eNOS), an enzyme that generates nitric oxide, is a major determinant of endothelial function. Several eNOS gene polymorphisms have been reported as 'susceptibility genes' in various human diseases states, including cardiovascular, pulmonary and renal diseases. We studied the 27-base pair tandem repeat polymorphism in intron 4 of eNOS gene in 60 β-thalassemia major (β-TM) patients compared with 60 healthy controls and assessed its role in subclinical atherosclerosis and vascular complications. Patients were evaluated stressing on transfusion history, splenectomy, thrombotic events, echocardiography and carotid intima–media thickness (CIMT). Analysis of eNOS intron 4 gene polymorphism was performed by PCR. No significant difference was found between β-TM patients and controls with regard to the distribution of eNOS4 alleles or genotypes. The frequency of eNOS4a allele (aa and ab genotypes) was significantly higher in β-TM patients with pulmonary hypertension or cardiomyopathy. Logistic regression analysis revealed that eNOS4a allele was an independent risk factor for pulmonary hypertension in β-TM patients [odds ratio (OR) 2.2, 95% confidence interval (95% CI) 1.19–5.6; P  < 0.001]. We suggest that eNOS intron 4 gene polymorphism is related to endothelial dysfunction and subclinical atherosclerosis and could be a possible genetic marker for prediction of increased susceptibility to cardiovascular complications.